Climate change going deep: The effects of global climatic alterations on cave ecosystems. (April 2019) - Mammola, Stefano; Piano, Elena; Cardoso, Pedro; Vernon, Philippe; Domínguez-Villar, David; Culver, David C; Pipan, Tanja; Isaia, Marco
Scientists of different disciplines have recognized the valuable role of terrestrial caves as ideal natural laboratories in which to study multiple eco-evolutionary processes, from genes to ecosystems. Because caves and other subterranean habitats are semi-closed systems characterized by a remarkable thermal stability, they should also represent insightful systems for understanding the effects of climate change on biodiversity in situ. Whilst a number of recent advances have demonstrated how promising this fast-moving field of research could be, a lack of synthesis is possibly holding back the adoption of caves as standard models for the study of the recent climatic alteration. By linking literature focusing on physics, geology, biology and ecology, we illustrate the rationale supporting the use of subterranean habitats as laboratories for studies of global change biology. We initially discuss the direct relationship between external and internal temperature, the stability of the subterranean climate and the dynamics of its alteration in an anthropogenic climate change perspective. Owing to their evolution in a stable environment, subterranean species are expected to exhibit low tolerance to climatic perturbations and could theoretically cope with such changes only by shifting their distributional range or by adapting to the new environmental conditions. However, they should have more obstacles to overcome than surface species in such shifts, and therefore could be more prone to local extinction. In the face of rapid climate change, subterranean habitats can be seen as refugia for some surface species, but at the same time they may turn into dead-end traps for some of their current obligate inhabitants. Together with other species living in confined habitats, we argue that subterranean species are particularly sensitive to climate change, and we stress the urgent need for future research, monitoring programs and conservation measures.